ANDEAN SUMMER-BREAK: ROCK ART INSIGHTS ON INFORMATION NETWORKS AND SOCIAL INTERACTION IN A DESERT-HIGHLAND INTERFACE IN NORTHERN PATAGONIA (SOUTH AMERICA) - Romero Villanueva, Guadalupe; F. Lucero, Gustavo; Barberena, Ramiro (Revista Cuadernos de Arte Prehistorico, 2021)
The Andes mountain range is one key physiographic feature of South America. Since the highlands are a very productive ecosystem only accessible in the summer, they may have been likely occupied during this season by human groups coming from different low-altitude areas in both slopes. The goal of this paper is to delve into trans-Andean social interaction and high-altitude human occupation strategies during the last 3000 years, which is a key period witnessing the inscription of the southern Andean landscape trough the execution of rock art. We develop a regional case study focused on a desert-highland interface in northwestern Patagonia (Argentina and Chile, 36-37ºS), which shows striking biogeographic and archaeological differences between both slopes. This case is based on the combination of two main lines of research: a) GIS landscape-modeling integrating seasonality and least cost paths to address connectivity between Andean highlands and lowlands and b) rock art macroregional trends to assess the materialization of information networks over the landscape. The results of our spatial analysis show that northwestern Patagonia has a high degree of environmental variability that entails changing connectivity profiles along the annual cycle, creating different scenarios in terms of insularity and risk for human populations. On this basis, the analysis of human informational networks as encoded in rock art suggests the existence of visually hierarchized environments that may have played a key role at a macro-regional scale. Overall, these results contribute to expand the discussion on human social networks and information exchange strategies deployed between highlands and their surrounding lowlands considering the role of landscape connectivity.